Comparative analysis of study quality assessment of students of Šiauliai university (Lithuania) and Open international university of human development “Ukraine” (Ukraine) - Bakanovienė, Tatjana; Gerulaitis, Darius; Povilaitienė, Neringa; Kolchenko, Kateryna (Social Welfare: Interdisciplinary Approach, 2012)
In the article the research data on study process assessment in two Lithuanian and Ukrainian Higher Education Institutions (N = 244) have been presented. The research aim is the exploration of the assessment of students studying at Šiauliai and “Ukraine” universities about the study process. Main fi ndings and conclusions states, that student’ of both countries Higher Education Institutions similarly assess peculiarities of the study process. Assessing organization of the study process in the aspect of e-teaching/learning technologies, it was noticed that respondents (of both universities) favourably assessed their manifestation in the study process but the obtained statistically signifi cant differences demonstrate different levels of preparation of universities for such organisation of the study process.
Keywords: Studies in higher education institutions; study process assessment